Language Style Used by Taylor Swift in Jimmy Kimmel Live - Medlin Bulain; Endar Rachmawaty Linuwih (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
This study examines the sort of language style and dominant language style employed by Taylor Swift on Jimmy Kimmel Live and the language function, which is the aim of Taylor Swift's utterances on that show. The study was conducted using a descriptive qualitative approach. The writer obtained the data from the Jimmy Kimmel Live talk show on YouTube and transcribed it into a text document. The analysis is based on Martin Joos' notion of language style, which includes frozen style, formal style, consultative style, informal style, and intimate style. In addition, Jakobson's theory is applied to the analysis of language functions, including referential, directional, expressive, phatic, poetic, and metalinguistic functions. This study demonstrates that Taylor Swift utilized three language styles: formal style with three utterances, consultative style with five utterances, and informal style with 19 utterances. Therefore, it can be inferred that Taylor Swift's predominant style is the casual style. In addition, the author identified four distinct functions of language: referential function, directive function, expressive function, and phatic function